Post-Stroke Depression among Stroke Survivors Attending two Hospitals in Kampala Uganda - Gyagenda, Joseph Ogavu; Ddumba, Edward; Odokonyero, Raymond; Kaddumukasa, Mark; Sajatovic, Martha; Katabira, Elly (African Health Sciences, 2015)
The burden of stroke worldwide is increasing rapidly. There is paucity of data on post-stroke depression (PSD) among stroke survivors in Uganda, despite the high prevalence of PSD reported elsewhere. In a cross-sectional study, we assessed adult participants with confirmed first stroke with a standardized questionnaire. The Patient Health Questionnaire-9 was used to assess for depression among non-aphasic patients while the Aphasic Depression Rating Scale was administered to aphasic patients. Univariable and multivariable analyses performed to describe associations with PSD. Forty three females (58.9%) and 30 males (41.1%) who had a stroke participated. Fifty eight (79.5%) had ischemic strokes and 12 participants (16.4%) were aphasic. The prevalence of PSD among the study participants was 31.5%. PSD was higher among patients assessed within 6 months after the onset of stroke. PSD was strongly associated with the total Barthel index of activities of daily living (BIADL) score; p=0.001. There was no significant association between demographic characteristics and PSD. There is a high prevalence of unrecognized post-stroke depression. Post-stroke depression was strongly associated with the patient’s inability to undertake activities of daily life. There is urgent need for integration of screening for and management of post-stroke depression among stroke survivors
Keywords: Post-stroke depression; Stroke; Survivors